When does mandatory price disclosure lower prices? Evidence from the German fuel market - Felix Montag; Alina Sagimuldina; Christoph Winter (University of Chicago Booth School of Business, Stigler Center for the Study of the Economy and the State, 2024)
The widespread availability of digital technologies has made mandatory price disclosure policies (MPD) a convenient tool for policymakers to increase price transparency and foster competition. The literature has shown that these can increase or decrease prices. We shed light on the circumstances under which MPD lowers prices. We study the introduction of MPD in the German retail fuel market by combining a stylized theoretical model with detailed data on prices, seller characteristics and consumer information. We find that low levels of prior consumer information, a high number of sellers, and complementary information campaigns foster the procompetitive effects of MPD.
Keywords: D83; L41; 330; Mandatory price disclosure; consumer information; retail fuel market